118k views
3 votes
Sandy evaluated the expression below

What was Sandy’s er ror?
Sandy should have evaluated (-2)³ as –8.
Sandy should have not multiplied 5 and 5.
Sandy did not add 2 and 3 correctly.
Sandy should have not subtracted 3 from 6 first.

Sandy evaluated the expression below What was Sandy’s er ror? Sandy should have evaluated-example-1
User Phyl
by
5.9k points

2 Answers

0 votes

Answer: a

Explanation:

User Bvr
by
6.0k points
3 votes

Answer:

Sandy should have evaluated (-2)³ as -8

Explanation:

(-2)³ (6 - 3) - 5(2 + 3) = -8 · 3 - 5 · 5 = - 24 - 25 = - 49

Because:

(-2) · (-2) · (-2) = 4 · (-2) = - 8

God with you!!!

User Pimp Trizkit
by
6.3k points